(untitled) (mathematica didactica, 2003)
This paper shows an approach to combine real operations in front of a mirror with perspective drawings in Dynamic Geometry Software. In a neurophysiological view on the spatial sense the relationship between real-life objects in front of a mirror and geometrical constructions in the software are of fundamental importance for the association of geometrical representations of 3D-space and perspective drawings.